Bradford, Wabaunsee County - Bauer, Karl (Kansas State University, The Chapman Center for Rural Studies, 2017)
Bradford, located in Section 23 of Wilmington Township, Wabaunsee County, Kansas, was a small community that tells a unique story of racial coexistence and rural population decline. Black and white residents both called the area home and coexisted in relative peace — taking classes at the same school, worshipping at the same church, shopping at the same businesses, and being buried in the same cemetery. In the 1890s and early 1900s, the community was bustling, but in the decades following, it witnessed closures and consolidations due in part to the increasing use and availability of the automobile. This study is mostly based on interviews with a local historian and publicly available historical society, library, and newspaper archives.
Karl Bauer, “Bradford, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/195.
Keywords: African American; Eskridge; Exodusters; Wabaunsee County; Lynchings; Charles C. Gardner